Phytogenic effects of Brachiaria decumbens saponin extract on growth performance, immune response, and telomere dynamics in broiler chickens under tropical conditions - Chung, Eric Lim Teik; Abu Kassim, Nafeesa; Zheng, Alvin Lim Teik; Jesse, Faez Firdaus Abdullah; Loh, Teck Chwen; Dunshea, Frank R. (Springer Science and Business Media B.V., 2026)
Excessive reliance on antibiotics in poultry farming has heightened global concerns over antimicrobial resistance, driving the need for sustainable and effective natural substitutes. This study assessed the impact of incorporating different levels of Brachiaria decumbens saponins extract into broiler diets on growth performance, hematological and biochemical indices, and telomere dynamics under tropical rearing conditions. A total of 300 one-day-old female Ross 308 chicks were randomly allocated to six treatment groups consisting of a negative control (no additives), a positive control (100 mg/kg oxytetracycline), and four groups supplemented with 25, 50, 75, or 100 mg of B. decumbens saponins extract per kg of feed. Over the 42-day trial, feed intake and body weight were recorded weekly. On day 42, blood samples were collected to evaluate leukocyte profiles, hepatic and lipid parameters, stress and immune biomarkers, and relative telomere length. Birds receiving 100 mg/kg of the extract (T6) demonstrated superior weight gain, improved feed conversion efficiency, and exhibited no adverse clinical manifestations. Additionally, T6 broilers showed enhanced immune competence, reflected in increased total WBC counts, reduced heterophil-to-lymphocyte ratios, improved lipid metabolism, decreased levels of stress-associated markers (SAA, AGP, corticosterone, HSP70), elevated immunoglobulin and cytokine concentrations, and markedly longer telomeres. Collectively, these results highlight B. decumbens saponins extract at 100 mg/kg as a potential phytogenic alternative to antibiotics for enhancing broiler health and productivity in tropical environments.